Cardiovascular Pathophysiology in Chronic Kidney Disease: Opportunities to Transition from Disease to Health - Matthew I. Tomey; Jonathan A. Winston (Ubiquity Press, 2014)
Background: Chronic kidney disease (CKD) is common, and is associated with a high burden of cardiovascular disease. This cardiovascular risk is incompletely explained by traditional risk factors, calling attention to a need to better understand the pathways in CKD contributing to adverse cardiovascular outcomes. Findings: Pathophysiological derangements associated with CKD, including disordered sodium, potassium, and water homeostasis, renin-angiotensin-aldosterone and sympathetic activity, anemia, bone and mineral metabolism, uremia, and toxin accumulation may contribute directly to progression of cardiovascular disease and adverse outcomes. Conclusion: Improving cardiovascular health in patients with CKD requires improved understanding of renocardiac pathophysiology. Ultimately, the most successful strategy may be prevention of incident CKD itself.